2012
DOI: 10.1016/j.amepre.2012.02.026
|View full text |Cite
|
Sign up to set email alerts
|

Graphic Warning Labels in Cigarette Advertisements

Abstract: Background The Family Smoking Prevention and Control Act gave the U.S. Food and Drug Administration (FDA) legal authority to mandate graphic warning labels on cigarette advertising and packaging. The FDA requires that these graphic warning labels be embedded into cigarette advertising and packaging by September 2012. Purpose The aim of this study was to examine differences in recall and viewing patterns of text-only versus graphic cigarette warning labels; and, the association between viewing patterns and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
128
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(139 citation statements)
references
References 22 publications
9
128
1
Order By: Relevance
“…A strong positive relationship was then observed between a measure of cognitive processing and smokers' intentions to quit and later cessation behavior. Eye-tracking studies have shown positive effects on viewing of the graphic warning text and dwell time in cigarette ads (Strasser et al, 2012). Other GHW eye-tracking research shows greater attention toward health warnings compared to brand information when shown on plain packs (i.e., without the colored logo associated with the brand name) versus regular branded packs, with effects observed among nonsmokers and weekly smokers, but not daily smokers (Munafo, Roberts, Bauld, & Leonards, 2011).…”
Section: Cigarettes and Graphic Health Warningsmentioning
confidence: 99%
“…A strong positive relationship was then observed between a measure of cognitive processing and smokers' intentions to quit and later cessation behavior. Eye-tracking studies have shown positive effects on viewing of the graphic warning text and dwell time in cigarette ads (Strasser et al, 2012). Other GHW eye-tracking research shows greater attention toward health warnings compared to brand information when shown on plain packs (i.e., without the colored logo associated with the brand name) versus regular branded packs, with effects observed among nonsmokers and weekly smokers, but not daily smokers (Munafo, Roberts, Bauld, & Leonards, 2011).…”
Section: Cigarettes and Graphic Health Warningsmentioning
confidence: 99%
“…This study did not test whether remembering health warnings more accurately translated into the desired effect of making a person quit smoking. Therefore, this study alone cannot justify whether graphic warning labels on cigarette packs really "work better" than written warnings when it comes to quit rates [29].…”
Section: Discussionmentioning
confidence: 90%
“…By contrast, the use of a warning label alone resulted in smoking levels that did not differ from baseline. In other research, graphic warning labels have been shown to increase recall for the relevant warning (Strasser, Tang, Romer, Jepson, & Cappella, 2012), enhance knowledge of smoking risks (Borland & Hill, 1997), reduce the likelihood of former smokers lighting up again (Hammond, McDonald, Fong, Brown, & Cameron, 2004), discourage current smokers from wanting to smoke (Cameron, Pepper, & Brewer, 2013), and reduce cigarette use among active smokers (Willemsen, 2005). But efforts to implement such warnings in the United States are currently stalled, and the evidence to date suggests that less prominent text-only warnings found on U.S. cigarette packs are much less likely to produce any of the those effects (Hammond, 2011).…”
Section: Discussionmentioning
confidence: 90%